(untitled) (Journal of Additive Manufacturing Technologies, 2021)
The recent developments in Additive Manufacturing (AM) have accelerated the spread of 3D printers all over the world. Fused filament fabrication (FFF) has become the prevalent technology for use in printing typical thermoplastics. Sometimes, the nature of layer-wise production brings about the necessity of using support structures, leading to (i) increased material consumption, (ii) reduced production speed, (iii) deterioration in the part quality, and (iv) extra post-processing. To eliminate these shortcomings of FFF, researchers proposed several methods, one of which is to benefit from particular multi-axis hardware. In this study, the capability of a multi-axis FFF machine in support-less printing is introduced. The quality of the produced part is compared with that of its identical counterpart printed on a conventional (i.e., 3-axis) FFF setup.